The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.4172/2329-6925.1000294
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathology of Pulmonary Hypertension: from Bio-Molecular Mechanism to Target Treatment

Abstract: Although the diagnosis and treatment of pulmonary hypertension (PH) is developed constantly in the last decade, PH remains an incurable and difficult to treat disease due to its high life disability and dreadful survival rate. The disease is characterized by sustained vasoconstriction, progressive vascular remodeling, and irreversible right heart dysfunction.The advanced knowledge in physiopathology and classification of PH in recent years is a useful tool helping physicians to improve the choice of target tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 125 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Currently, endothelial dysfunction is defined as an imbalance between vasorelaxation (mediated mainly by nitric oxide pathway) and vasoconstriction (induced by endothelin-1 and its receptors), between anti-coagulant and pro-coagulant substances, or between growth-inhibiting and growth-promoting mediators [2]. It has been demonstrated that endothelial dysfunction is one of the earliest manifestations of vascular disease and atherosclerosis [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, endothelial dysfunction is defined as an imbalance between vasorelaxation (mediated mainly by nitric oxide pathway) and vasoconstriction (induced by endothelin-1 and its receptors), between anti-coagulant and pro-coagulant substances, or between growth-inhibiting and growth-promoting mediators [2]. It has been demonstrated that endothelial dysfunction is one of the earliest manifestations of vascular disease and atherosclerosis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The last one is a potential risk factor for high blood pressure in adult. However, endothelial dysfunction is also associated with different forms of vascular diseases, such as systemic or regional arterial hypertension [2,4] and coronary arterial or peripheral vascular diseases [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%